DISABILITY AND EPIDEMIOLOGICAL INVISIBILITY: CHALLENGES FOR SOCIAL PROTECTION AND PREVENTION OF HARM - Freitas Macedo, Sthélio; Costa de Azevedo Mello, Emmanuella; Cristine Cottin Severiano Albuquerque, Rosicler; Fabíola Silva Araújo, Mayonara; Cristina Vieira da Silva , Viviane; Trindade Benites , Patrícia; Ximenes Oliveira , Silvia; Barreto Pereira, Jéssica (Revista Gênero e Interdisciplinaridade, 2026)
People with disabilities face structural inequalities that are reflected both in the absence of data in information systems and in the failures of public policies for social protection and health prevention. This article aims to analyze the challenges posed by the epidemiological invisibility of disability and its consequences for guaranteeing rights and equity. This is an integrative literature review conducted in the SciELO, BVS, LILACS, and PubMed databases, in addition to the analysis of official documents, between 2015 and 2023. The results were organized into two thematic categories: (1) invisibility in health information systems and (2) weaknesses in social protection and preventive strategies. The findings indicate that disability continues to be underrepresented in official records, which compromises the formulation of inclusive policies. It is concluded that overcoming this exclusion requires reformulations in surveillance models and public policies based on accessible data, social participation, and intersectoral approaches.